(untitled) (Medical Forum Monthly, 2024)
Objectives: To observe the changes in the number of sperms in semen in response to exposure to the electromagnetic radiation (EMR) from cell phones. Study Design: Experimental comparative study. Place and Duration of Study: The study was conducted in Institute of Basic Medical Sciences (IBMS), Animal house of Dow University of Health Sciences (DUHS) and Dow Diagnostic Research and Reference laboratory, Ojha campus, Karachi from February 2011 to October 2011. Materials and Methods: Seventy male Albino rats obtained from the animal house of IBMS, DUHS, Karachi, were divided into two main groups. Group A (control) and Group B (exposed), each containing 35 rats. Both groups were subdivided in five subgroups A1, A2, A3, A4, A5 for control group A and B1, B2, B3, B4, B5 for exposed group B, each consisting of 7 rats. The EMR was given by cell phones to exposed group for 3 hours/day and were sacrificed on 30, 50, 70, 90 and 110 days of exposure. Mean values of concentration of sperm in group A were compared with exposed group B. Statistical analysis was performed by SPSS using One Way Analysis Of Variance to find significance among groups. T-test was used to compare mean differences between groups. Results: The concentration of sperm was found to be significantly decreased in exposed groups. Conclusion: This study concluded that exposure to EMR from cell phones affects the semen quality by producing significant decrease in concentration of sperm.